Review of the Training Room "The Role of Training Management Personnel" - Santika, Mira; Andriani, Tuti (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
In the context of human resources development (HRD), the role of training management personnel is crucial in ensuring the effectiveness and success of training programs [1]. This article aims to delve deeper into the roles and characteristics of the four main groups of training management personnel: instructors, educators, educational staff, and other personnel. Instructors, as the frontline in the teaching and learning process, play a crucial role in delivering content and facilitating learning. They not only possess adequate technical expertise in their respective fields but also have good communication skills to deliver information in an engaging and meaningful way to training participants. Educators, often integral parts of the teaching team, are responsible for curriculum planning, development, and management. They design effective learning strategies, develop relevant evaluation tools, and are responsible for continuous monitoring and improvement of training programs. Educational staff, on the other hand, are responsible for the administrative and operational management of training programs. They plan and organize training activities, manage facilities and available resources, and ensure that all administrative aspects run smoothly to support the smooth implementation of programs. In addition to these three main groups of training management personnel, there are also other personnel who support the implementation of training programs. This includes administrative staff handling general administration, technicians responsible for facility maintenance, and other facilitators who assist in the implementation of training activities. Through a deeper understanding of the roles and characteristics of each group of training management personnel, it is hoped that training institutions can improve the overall effectiveness, efficiency, and quality of the programs they offer, thereby making significant contributions to HRD and organizational quality improvement [ 4].